KAJIAN RESIKO PERUSAHAAN DARI PERPEKSTIF CORPORATE GOVERNANCE - Prastya, Dwi; Zaitul , Zaitul; Ilona, Desi (Gapenas Publisher, 2025)
This study aims to examine the influence of corporate governance mechanisms on corporate risk. The corporate governance variables used include the size of the board of commissioners, institutional ownership, audit committee size, and audit quality. In addition, this study also uses variable earning management. The research data uses a quantitative approach with a panel data regression analysis method on banking companies listed on the IDX for the 2023–2024 period. The results of the study show that the size of the board of commissioners has a positive effect on the company's risk. In addition, institutional ownership and audit quality have a negative effect on company risk. These findings are expected to make a theoretical contribution to the corporate governance literature and practical implications for regulators and bank management in reducing risk through effective governance